Seleção de habitat de Panthera onca (Linnaeus, 1758) em uma paisagem heterogênea no Pantanal sul-matogrossense - Santos, Patrícia Kalaf Alves dos [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
The study about the habitat selection by carnivores in heterogeneous landscapes has a great importance, seeing that in order to trace species conservation strategies, it is necessary that their habits are deciphered and also how the species relate to the space. The determination of how the landscape structure can affect the permeability for a species aids in identifying lanes and barriers thereto. In this study, we tested the hypothesis that the habitat selection by Panthera onca would be related to the type of vegetation class, with preference not necessarily due to their greater availability, but to what resources this class can provide to the individual. We used movement data of two females monitored by GPS collars for Onçafari's researches project in Pantanal of Mato Grosso do Sul (Caiman Ecological Refuge). The jaguars, named Nusa and Esperança, were monitored for four months (April to August in 2015) generating 2248 trigger points for Esperança and 2301 to Nusa. The mapping of use and landscape cover conducted by the crew from the Laboratory of Conservation and Spatial Ecology - LEEC, was made through Rapid Eye images provided by CENAP (ICMBio) and Landsat 5 (INPE), being then, established the landscape classes in 6 categories: Dry Field / Pasture With Trees, Dry field / Pasture Without Trees, Humid Field With Trees, Humid Field Without Trees, Water and Forest. The habitat selection analyses were prepared for each individual, through the randomization points of the same quantity as that of the occurrence within their respective home range and then, using the RESOURCE SELECTION FUNCTION in the R program, it was possible to determine through the density of the points found in each landscape class, its use and availability. The size of the home range for the female Esperança was 116.4 km² and for Nusa 139.3 km² (95% kernel, with a width set to 2 km) and in both cases there was a habitat selection, since the use frequency of the...

O estudo sobre a seleção de habitat por carnívoros em paisagens heterogêneas possui uma grande importância, visto que para traçar estratégias de conservação de uma espécie é preciso decifrar seus hábitos e entender como estas se relacionam com o espaço. A determinação de como a estrutura da paisagem pode afetar a permeabilidade para uma espécie auxilia na identificação de corredores e barreiras para a mesma. Neste estudo, foi testada a hipótese de que a seleção de habitat por Panthera onca estaria relacionada ao tipo de classe de vegetação, havendo preferência não necessariamente por sua maior disponibilidade, e sim para o que esta classe oferece de recursos ao indivíduo. Utilizamos dados de movimentação de duas fêmeas, monitoradas através de colares GPS por pesquisadores do projeto Onçafari no Pantanal sul-matogrossense (Refúgio Ecológico Caiman). As onças, nomeadas Nusa e Esperança foram monitoradas por quatro meses (de abril a agosto de 2015) gerando 2248 pontos de ocorrência para Esperança e 2301 para Nusa. O mapeamento de uso e cobertura da paisagem, realizado pela equipe do Laboratório de Conservação e Ecologia Espacial - LEEC, foi feito através de imagens Rapid Eye fornecidas pelo CENAP (ICMBio) e imagem Landsat 5 (INPE), sendo então, estabelecidas as classes de paisagem em 6 categorias: Campo Seco/Pasto com Árvores, Campo Seco/Pasto sem Árvores, Campo Úmido com Árvores, Campo Úmido sem Árvores, Água e Floresta. As análises de seleção de habitat foram elaboradas para cada indivíduo, através da aleatorização de pontos de mesma quantidade que os de ocorrência dentro de suas respectivas áreas de vida e então, utilizando a função RESOURCE SELECTION FUNCTION no programa R, pôde-se determinar, através da densidade dos pontos encontrada em cada classe de paisagem, seu uso e disponibilidade. O tamanho da área de vida para a fêmea Esperança foi de 116.4 km2 e para Nusa, de...
Keywords: Ecologia animal; Habitat (Ecologia); Onças-pintadas; Animais carnívoros; Ecologia da paisagem; Pantanal Mato-grossense (MS e MT)